Proteomic and metabolomic analysis on cadmium-induced mitochondrial toxicity in liver tissues of juvenile olive flounder Paralichthys olivaceus - Lu, Zhen; Xiao, Zeyu; Wu, Sihan; Song, Jun; Peng, Xiao (Frontiers in Marine Science, 2022)
Introduction Cadmium (Cd) is one of the most dominant heavy metals in the Bohai Sea. Our previous study proved that Cd could induce gill mitochondrial toxicity in marine animals. Herein, we aimed to elucidate the toxicity mechanism of Cd on liver mitochondria, as liver is the main metabolic and detoxification organ and generally rich in mitochondria. Methods The mitochondrial responses induced by Cd (5 and 50 μg/L) were characterized by observing mitochondrial morphology, measuring mitochondrial membrane potential (MMP), and proteomic and metabolomic analysis in juvenile olive flounder Paralichthys olivaceus livers. Results After water-bonre exposure for 14 days, two Cd treatments decreased MMPs significantly and caused ultrastructural-damaged mitochondria in flounder livers. NMR-based metabolomics revealed that Cd exposure mainly altered the abundances of metabolites (ATP, AMP, phosphocholine, lactate and succinate) related to energy metabolism in flounder livers. iTRAQ-based mitochondrial proteomics indicated that 27 differentially expressed proteins (DEPs) were screened out from liver mitochondria after Cd treatments. These proteins were mainly associated with energy metabolism (oxidative phosphorylation (OXPHOS) and tricarboxylic acid (TCA) cycle) and apoptosis. Discussion These results indicated that Cd disrupted mitochondrial morphology, energy homeostasis and apoptosis in liver mitochondria in flounder P. olivaceus. This work revealed a comprehensive view on Cd-induced mitochondrial responses in the liver tissues of flounder using an integrated proteomic and metabolomic approach.